The impact of video technology on learning: A cooking skills experiment. (1st July 2017) - Surgenor, Dawn; Hollywood, Lynsey; Furey, Sinéad; Lavelle, Fiona; McGowan, Laura; Spence, Michelle; Raats, Monique; McCloat, Amanda; Mooney, Elaine; Caraher, Martin; Dean, Moira
Abstract: This study examines the role of video technology in the development of cooking skills. The study explored the views of 141 female participants on whether video technology can promote confidence in learning new cooking skills to assist in meal preparation. Prior to each focus group participants took part in a cooking experiment to assess the most effective method of learning for low-skilled cooks across four experimental conditions (recipe card only; recipe card plus video demonstration; recipe card plus video demonstration conducted in segmented stages; and recipe card plus video demonstration whereby participants freely accessed video demonstrations as and when needed). Focus group findings revealed that video technology was perceived to assist learning in the cooking process in the following ways: (1) improved comprehension of the cooking process; (2) real-time reassurance in the cooking process; (3) assisting the acquisition of new cooking skills; and (4) enhancing the enjoyment of the cooking process. These findings display the potential for video technology to promote motivation and confidence as well as enhancing cooking skills among low-skilled individuals wishing to cook from scratch using fresh ingredients.